First record of polyester bee Hylaeus cornutus (Curtis, 1831) in Belarus - Koroteeva , Daria O. (Experimental Biology and Biotechnology, 2024)
The first record of the bee Hylaeus cornutus (Curtis, 1831) of the family Colletidae (Hymenoptera, Apoidea) in Belarus is given.